PETROLOGY AND TECTONICS IMPLICATION OF VOLCANIC ROCKS AND OPHIOLITE COMPLEX FROM AMPANA SOROUNDING AREA CENTRAL SULAWESI BASED ON GEOCHEMICAL PATERN - Latief Sunan, Huzaely
Ampana area and Togean Islands are located in Central Sulawesi, tectonically arranged in the East Arm of Sulawesi. In the Togean islands there is a Colo Volcano located on Una-Una Island. The purpose of this study is to know the geochemical pattern of volcanic rock and ophiolite complex and to know the genesis of volcanic rock with the ophiolite complex of Ampana surrounding area. The method used in the form of analysis which are petrography, by thin section analysis, X-Ray Fluoroscence (XRF) and Inductively Coupled Plasma Mass Spectrometry (ICP-MS) from 8 volcanic rocks and 19 rocks from complex ophiolite. Based on thin section analysis of volcanic rocks showing andesite and tuff, whereas the complex ophiolite consists of gabbro, diabas, and basalt. Geochemical analysis (XRF) consists of the major elements, trace elements, and rare earth elements. Based on the AFM diagram (FeO*, K2O + Na2O, MgO), the afinity from volcanic rocks are tholeiitic while the complex ofiolite are tholeiitic. The graphic of K2O + Na2O to SiO2 in volcanic rocks show magma evolution is composed of andesite to dacit, while in ofiolit is composed peridot gabro to gabro. The rare earths of volcanic rocks presented in the normalization diagrams of the condrits show the decreased REE fractionation pattern from the light rare earths elements (LREE) to heavy rare earths elemnts (HREE). Therefore, it is interpreted that the magma in the research area is formed in the islands arc as well as the influence of the upper continental crust associated with the subduction process. Rare earth elements in the ofiolit rock showed a relatively flat pattern of fractionation. This pattern is interpreted as magma is formed in the mid-oceanic ridge (MOR).